Ecohumanism in teaching poetry for EFL students in Indonesia - Novita Dewi (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article presents a research report on poetry teaching to Indonesian EFL students to investigate their environmental concerns. It first explores the theoretical concepts of global citizenship in the teaching of language and literature in the light of Ecohumanism. Applying metacognitive strategy or self-regulatory learning method, this study uses students’ evaluation results, assignments, and reflection notes as data sources. It aims to find out to what extent reading and subsequently writing poems about the environment can raise students’ awareness to care for the sustainability of earth resources. The present study reveals that, firstly, there is a lack of concern for the care of the earth, proven by the students’ choice of poems to read and write. Secondly, the study shows that self-regulatory learning is suitable to implement here as shown from the students’ expanding interests to deal critically with people-nature relationships through poetry reading and writing at the later stage. This study concludes that Ecohumanism as an educational paradigm can establish rationale to include ecology in language and literature teaching. The “what, how, why, and what next” in language and literature teaching should then be geared and habituated continually towards respecting Earth in this mutually dependent world.